2013
DOI: 10.1098/rspb.2013.0991
|View full text |Cite
|
Sign up to set email alerts
|

The sense of agency is action–effect causality perception based on cross-modal grouping

Abstract: Sense of agency, the experience of controlling external events through one's actions, stems from contiguity between action-and effect-related signals.Here we show that human observers link their action-and effect-related signals using a computational principle common to cross-modal sensory grouping. We first report that the detection of a delay between tactile and visual stimuli is enhanced when both stimuli are synchronized with separate auditory stimuli (experiment 1). This occurs because the synchronized au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 42 publications
7
83
0
Order By: Relevance
“…Although we did not specifically measure intentional binding, our results are in line with this phenomenon to a certain extent. First of all, we found bimodal enhancement, which has previously been found as well by Kawabe et al (2013). Furthermore, for bimodal trials we see a specific advantage when the task-irrelevant modality is not delayed; with increasing delay of this stimulus, delay detection becomes worse.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although we did not specifically measure intentional binding, our results are in line with this phenomenon to a certain extent. First of all, we found bimodal enhancement, which has previously been found as well by Kawabe et al (2013). Furthermore, for bimodal trials we see a specific advantage when the task-irrelevant modality is not delayed; with increasing delay of this stimulus, delay detection becomes worse.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, lower thresholds were found when additional tones were presented at the time of the buttonpress and visual stimulus in a cross-modal grouping paradigm with variable delayed visual stimuli (Kawabe, Roseboom, & Nishida, 2013). Although the sense of agency may rely, at least partly, on the same forward model used in sensorimotor predictions (Farrer, Frey, et al, 2008), it has also been suggested to emerge from an additional interpretive mechanism (Kawabe et al, 2013). In our study, we specifically investigated multisensory temporal predictions of the forward model by using a delay detection task instead of assessing the subjective experience of the action outcome.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the impact of latency is often only considered with respect to one single factor (e.g., perception of simultaneity Raaen et al 2014]). In other cases, only very simple tasks such as button pressing are examined without a focus on VR [Kawabe et al 2013;Rohde et al 2014a]. Also, Rohde et al [2014b] found that feedback delays are processed differently in predictable motor tasks as opposed to unpredictable motor tasks.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative account proposes that, by analogy with cross-modal cue combination (Ernst & Banks, 2002;Körding et al, 2007), the timing judgements of intentional actions and their outcomes may be a weighted average of the action and outcome cues (Kawabe, Roseboom & Nishida, 2013), with the weighting dependent on the estimated precision with which each is individually timed. The decreased outcome judgement shift reported here may therefore arise from the increased weighting of the outcome cue over the action cue in estimating the time of the outcome event when motor intention information is discounted and the estimated precision of the action cue consequently decreases (consistently, in the supplemental material we report lower within-participant SD in the voluntary than in the post-hypnotic condition for high hypnotisables and sensitive evidence of no difference in medium hypnotisables).…”
Section: Discussionmentioning
confidence: 99%